Coverage and predictors of full measles-rubella immunization among children aged 24–59 months in Northern Ghana: a post measles outbreak assessment - Abdul Gafaru Mohammed; Ruth Nimota Nukpezah; Pascal Kingley Mwin; Sumani Abdul-Manan; Eunice Baiden-Laryea; Ernest Kenu (BMC Public Health)
Abstract Introduction Vaccination plays a critical role in ensuring the health, survival, and well-being of children worldwide. It is one of the most cost-effective and scientifically proven public health interventions that protect children from severe and life-threatening diseases. Despite efforts to improve measles vaccination coverage in the five Northern regions of Ghana, less than 70% complete vaccination coverage leaves these areas vulnerable to outbreaks. To fill this gap, our study explores the predictors of complete measles immunization coverage among children aged 24–59 months in Northern Ghana. Methods A community-based cross-sectional study was conducted from June to September 2023. Data was collected from caregivers of children aged 24–59 months. A sample size of 636 children with a multistage sampling technique was used. We collected data from the caregivers using a semi-structured questionnaire and a data abstraction tool. Logistic regression was used to assess the factors associated with measles vaccine uptake at a 5% significance level. Results Among the 617 children, 61.1% (0.57–0.65) were fully vaccinated against measles. The first dose of the measles-rubella vaccine was received by 87.7% (95% CI: 0.84–0.90) of the children. After adjusting for potential confounders, regression models showed that the awareness (aOR = 2.91, 95% CI:1.35–6.25), high knowledge level (aOR = 8.27, 95% CI:3.02–22.71), ANC (aOR = 2.48, 95% CI:1.11–5.52), side effects (aOR = 0.04, 95% CI:0.02–0.08) and receiving other childhood vaccines (aOR = 3.27, 95%CI:1.80–5.94) were significantly associated with the uptake of measles-rubella vaccines in Northern Ghana. Conclusion The uptake of the second dose of the measles-rubella vaccine in Northern Ghana was below the recommended 95% by the WHO. Awareness of the vaccine, knowledge level, ANC attendance, receiving other vaccines, and perceived side effects were the main predictors of measles vaccine uptake in the region. Ghana Health Service should intensify sensitization and awareness creation at the community level.